BIAYA MEDIK LANGSUNG KEMOTERAPI PASIEN KANKER KOLOREKTAL RUANG PERAWATAN KELAS 3 PESERTA JKN RUMAH SAKIT “X” DI KOTA SEMARANG - Kurniawati, Fransisca Tri; Rukminingsih, Fef (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Colorectal cancer (CRC) is the second most common cancer in men after lung cancer. The cost of CRC therapy is very high. The National Health Insurance (NHI) through BPJS covers the direct medical costs of CRC patients. One of the therapies for CRC patients is chemotherapy. Based on its level, chemotherapy is classified into mild, moderate and severe chemotherapy. This study aims to determine the average direct medical costs of mild chemotherapy in CRC patients in class 3 treatment rooms at “X” Hospital in Semarang City. This study is a descriptive observational study, using retrospective data. Data were obtained from medical records (MR) and billing data for CRC patients participating in NHI who underwent mild chemotherapy (C-4-13-I) for the period January–June 2023. The inclusion criteria were CRC patients with ICD code Z5.1.1, aged 18-65 years, class 3 treatment rooms. Patients who upgrade their class treatment rooms are excluded. Data processing was carried out by calculating the average direct medical costs based on patient billing. The results of the study obtained 79 chemotherapy billing data for CRC patients. Most patients were >45 years old, namely 69 patients (87.34%), male as many as 63 patients (79.75%). The most common chemotherapy regimens were FOLFIRI (59.49%) and FOLFOX (34.18%). The average length of treatment was 4.3 days. The largest direct medical cost components were medical and health personnel costs (45.17%) and drug costs (37.22%). The average direct medical cost for mild chemotherapy in class 3 treatment rooms was IDR 2,490,615.